Influence Of An Orally Active Thromboxane Synthesis Inhibitor On Platelet Function In Man - Walter, E; Zimmermann, R; Lehle, R; Weber, E (Thrombosis and Haemostasis, 1981)
Several studies have shown that elevated levels of circulating thromboxane and a decreased capacity of the vessel wall to synthesize prostacyclin do occur in patients with cardiovascular diseases and in diabetes. In contrary to the effect of aspirin, selective inhibition of thromboxane synthesis of the platelets would preserve the production of prostacyclin. This selectivity is offered by UK-37, 248, a new imidazole derivative.In 11 patients with cardiovascular diseases and en -hanced platelet aggregation a single dose of 100 mg UK-37,248 was tested. Before and 1, 2, 4, 6 and 24 h after intake, blood pressure, pulse, bleeding time were controlled, and blood was taken for in-vitro platelet aggregation and for measurements of plasma as well as serum TXB2 . The plasma TXB2 -level decreased from 130.9±14.2 pg/ml to 85.7±4.6 pg /ml (p< 0.005) after 6 h. Serum TXB (319.3±31.4 ng/ml) was lowest 1 h after drug intake (32.9±5.9 ng/ml, p< 0.001). 5 h later the level was still significantly decreased (182.1±24.3 ng/ml,p<0.005). The drug had no influence on blood pressure and pulse rate in the lying as well as standing position. Bleeding time was minimally prolonged in 7 patients, the mean prolongation was about 10 %. No effect could be observed on spontaneous, ADP-and co11agen-induced platelet aggregation.The inhibition of thromboxane synthesis in man by UK-37,248 after a single dose of 100 mg could very well be demonstrated. There was no or only a minimal effect on platelet aggregation and bleedingtime. Evaluation of long-term administration is needed.We thank Dr. Tyler, Sandwich, for TXB2-measurements.